Propolis consumption by asymptomatic HIV-individuals: Better redox state? A prospective, randomized, double-blind, placebo-controlled trial - Tasca, Karen Ingrid [UNESP] (2023)
Propolis is a natural product has many biological properties of clinical interest, such as anti-inflammatory and antioxidant. Considering that people living with HIV/aids (PLWHA) on effective combined antiretroviral therapy (cART) present early aging due to an intense immune activation, inflammation, and redox imbalance, propolis consumption could offer a benefit to such patients. This double-blind longitudinal study evaluated whether Brazilian green propolis pills intake (500 mg/day for three months) would decrease the oxidative stress of virological suppressed HIV-individuals. To compare each group (propolis, n = 20 versus placebo, n = 20) in both moments (M0, before and M1, after the intervention), the following markers were assessed: plasma malondialdehyde (MDA), carbonylation, total oxide nitric, total antioxidant capacity (TAP), superoxide dismutase, catalase, and NFkB and NRF2 gene expression. Data were analyzed using Poisson, Gamma distribution and ANOVA followed by Tukey-Kramer. The groups were homogeneous regarding age, gender, time of diagnosis/ treatment, cART scheme, CD4+ T cell count, and no changes were observed in the diet food, or patients’ lifestyles. A decreased MDA concentration was seen in the propolis group (M0 = 0.24 ± 0.13, M1 = 0.20 ± 0.10 protein nmol/mg; p = 0.005) as well as a slight but non-significant increase of TAP (M0 = 49.07 ± 13.26, M1 = 52.27 ± 14.86%; p = 0.06). One may conclude that propolis promoted a lower lipid peroxidation and improved the antioxidant system, suggesting that its use may be beneficial to PLWHA in an attempt to contain the intense inflammatory and oxidant activity.